A SURVEY ON HEALTHACRE SYSTEMS USING CONTEXT AWARE MONITORING (CAM) TECHNIQUES - B Badar, Mrs.Priti; Selvaraj, Nalini; kumar, Rajeev (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
This paper gives an insight of how we can effectively store and retrieve the data from health-care in order to improve the performance. Context-aware monitoring (CAM) is a technology that has recently entered into the technological world and it provides real-time personalized health-care services. CAM is a rich area for big data applications. Velocity, veracity, volume and variety are the four dimensions of big data, as stated by Data scientists of IBM. The proposed model is alleviating the big data in cloud computing environment. It’s excavating the patterns from the patient data and correlating the probabilities to discover the abnormal symptoms properly in different patients.